Development of postcompressional textural tests to evaluate the mechanical properties of medicated chewing gum tablets with high drug loadings. Issue 1 (15th August 2017) - Al Hagbani, Turki; Nazzal, Sami
Abstract: Medicated chewing gum tablets (CGTs) represent a unique platform for drug delivery. Loading directly compressible gums with high concentrations of powdered medication, however, results in compacts with hybrid properties between a chewable gum and a brittle tablet. The aim of the present study was to develop textural tests that can identify the point at which CGTs begin to behave like a solid tablet upon drug incorporation. Curcumin (CUR) CGTs made with Health in gum were prepared with increasing CUR load from 0 to 100% and were characterized for their mechanical properties by a single‐bite (knife) and a two‐bite tests. From each test several parameters were extracted and correlated with drug loading. In the single‐bite test, the change in the resistance of the compacts to plastic deformation was found to give a definitive guide on whether they behave as gums or tablets. A more in depth analysis of the impact of CUR loading on the chewability of the CGTs was provided by the two‐bite test where CUR loading was found to have a nonlinear impact on the mechanical properties of compacts. An upper limit of 10% was found to yield compacts with gum‐like properties, which were abolished at higher CUR loads. The textural test procedure outlined in this study are expected to assist those involved in the formulation of medicated gums for pharmaceutical applications in making an informed decision on the impact of drug loading on gum behavior before proceeding with clinical testing. Practical applications: There is a growing interest in utilizing medicated chewing gums for drug delivery, especially those made using directly compressible gum bases, such as Health in gum. Directly compressing a gum base with high amounts of solid drug powder, however, poses a challenge as it may result in compressed compacts with hybrid properties between a chewing gum and a hard tablet. Currently, official Pharmacopeias do not specify a testing procedure for the estimation of the mechanical and textural properties of chewing gum tablets. To fill in the knowledge gap, we demonstrated in the present study how complementing a single‐bite (knife) test with a modified two‐bite test could be used to discriminate between chewing gums and hard tablets that were prepared by directly compressing Health in gum base with increasing concentration of curcumin powder in the blend. By utilizing these two tests, it was possible to identify clear demarcations between conventional tablets and chewing gums. In this study, we found that a 10% load by weight is the upper limit for curcumin loading in a binary blend with Health in gum to maintain the mastication properties of the compacts, which become brittle tablets at 30% load.